Upaya Peningkatan Pengetahuan Rumah Sehat Bagi Keluarga di Desa Bangun Sari Kecamatan Kampar Kiri Hilir - Hardianti, Sri; Febria, Dessyka; Irawan, Joni; Hastuty, Milda; Pardede, Ranat Mulia (Dedikasi: Jurnal Pengabdian Pendidikan dan Teknologi Masyarakat, 2023)
A healthy house that meets the requirements is a house that has healthy latrines, clean water facilities, garbage disposal sites, waste water disposal facilities, good house ventilation, appropriate housing density and house floors that are not made of waterproof materials. The mechanism for implementing activities in general is in the form of preparation, implementation and evaluation. Planning coordinates with the Village Head. The implementation of health counseling to the people of Bangun Sari village, Kampar Kiri sub-district, downstream, the work procedure is by gathering the community to be given counseling about healthy homes, preparing the equipment needed in counseling, carrying out counseling using the lecture and question and answer method. The results of the implementation of community service activities can be described through 2 (two) stages of activity, namely preparation and implementation. Counseling on Increasing Knowledge of Healthy Homes for families is categorized as successful because the objectives of this activity have been achieved and the implementation process is running smoothly. Based on the results of the counseling that has been done, it can be concluded that this counseling can add to the knowledge of the people in Bangun Sari Village, Kampar Kiri Hilir District, Kampar Regency, thus increasing the community's knowledge of implementing healthy homes.